Aristotle's Politics on Greeks and Non-Greeks. Issue 4 (2021) - Lockwood, Thornton
Abstract: Scholars of race in antiquity commonly claim that Aristotle holds protoracist views about barbaroi or non-Greeks. But a careful examination of Aristotle's remarks in his Politics about slavery, non-Greek political institutions, and Greek and non-Greek natural qualities calls into question such claims. No doubt, Aristotle held views at odds with modern liberalism, such as his views about gender subordination and the exploitation of slave and nonslave labor. But claims that Aristotle holds protoracist views are regularly but erroneously asserted without careful consideration of relevant textual evidence. I argue that Aristotle neither categorically distinguishes Greeks and non-Greeks nor does he endorse the claim that Greeks are categorically superior to non-Greeks. Indeed, Aristotle regularly draws upon non-Greek political institutions in his own formulation of the best constitution and he praises the non-Greek constitution of Carthage as superior to that of Greek constitutions such as Sparta and Crete.